THE DEVELOPMENT OF MODULES OF ARGUING IN DEBATEUSING GENRE PEDAGOGI APPROACH FOR PARTICIPANTS IN CLASS X SMA NEGERI 1 KAYUAGUNG - Fatwa Negara, Aby; Eko Purnomo, Mulyadi; Suhendi, Didi (Sriwijaya University Learning and Education International Conference, 2018)
This study aims to produce an effective module with the title of Logis Berargumentasi melalui Debat using a genre pedagogy approach. This research and development modify the procedures proposed by Jolly and Bolitho and Dick, Carey, and Carey. To know the feasibility of the module is done expert validation with data collection techniques through questionnaire. To test the practicality of the module is done one-to-one evaluation and small group evaluation with data collection techniques through questionnaire. Then, to know the effectiveness of the module conducted field testing through experiments with data collection techniques using the test. Based on the validation results from material experts, language, presentation, and kegrafikaan note that this module is categorized very well. Practical test results show that the modules developed are very practical. Finally, the results of field tests through pretest and postes there is an increase in the average value of students for 45.033, so that the module can be categorized as effective or have a potential effect for learners.